2023
DOI: 10.1021/acscatal.3c03641
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Carbon-Supported Platinum–Rare Earth Nanoalloys during Electrochemical Activation

Carlos A. Campos-Roldán,
Jean-Sébastien Filhol,
Hazar Guesmi
et al.

Abstract: Carbon-supported platinum–rare earth nanoalloys are promising electrocatalysts for the oxygen reduction reaction. However, their structure–activity–stability trends are poorly understood. Herein, we followed the evolution of Pt–Nd/C nanoalloys during the electrochemical surface conditioning, i.e., prior to the initial evaluation of electrocatalytic activity, and observed that their compositional, morphological, and structural ex situ properties are considerably modified by the electrochemical activation step. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Previously, we have reported that Pt-rare earth nanoalloys undergo significant structure transitions during the early surface conditioning step, namely, the electrochemical activation. , Such transitions, often not investigated or underestimated, do induce a considerable effect on the electrocatalyst activity and its retention. , Therefore, online ICP-MS and operando WAXS measurements were conducted to follow any possible degradation of Pt x Y/C during the electrochemical activation, see Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have reported that Pt-rare earth nanoalloys undergo significant structure transitions during the early surface conditioning step, namely, the electrochemical activation. , Such transitions, often not investigated or underestimated, do induce a considerable effect on the electrocatalyst activity and its retention. , Therefore, online ICP-MS and operando WAXS measurements were conducted to follow any possible degradation of Pt x Y/C during the electrochemical activation, see Figure .…”
Section: Resultsmentioning
confidence: 99%